2017
DOI: 10.1074/jbc.m116.749465
|View full text |Cite
|
Sign up to set email alerts
|

Three Tyrosine Residues in the Erythropoietin Receptor Are Essential for Janus Kinase 2 V617F Mutant-induced Tumorigenesis

Abstract: Edited by Alex TokerThe erythropoietin receptor (EpoR) regulates development of blood cells, and its full activation normally requires the cytokine erythropoietin (Epo). In the case of myeloproliferative neoplasms (MPN), Epo-independent signaling through EpoR can be caused by a point mutation, V617F, in the EpoR-interacting tyrosine kinase Janus kinase 2 (JAK2). In cells expressing the JAK2 V617F mutant, eight tyrosine residues in the intracellular domain of EpoR are phosphorylated, but the functional role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In this regard, EPOR knockdown in breast cancer cell lines reduces pAKT levels, which suggests its involvement in transmission of signals, including phosphorylation and activation of AKT (12). Moreover, Ueda et al (26) demonstrated the role of JAK2 point mutation in EPOR activation and myeloproliferative neoplasms. Indeed, the EPO-independent EPOR activation needs to be elucidated in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, EPOR knockdown in breast cancer cell lines reduces pAKT levels, which suggests its involvement in transmission of signals, including phosphorylation and activation of AKT (12). Moreover, Ueda et al (26) demonstrated the role of JAK2 point mutation in EPOR activation and myeloproliferative neoplasms. Indeed, the EPO-independent EPOR activation needs to be elucidated in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…An amount of 2 mL of retrovirus solution was added to each well coated with RetroNectin, and cultured for 6 h at 37 • C in a 5% CO 2 incubator. After removing the virus solution, 1 mL of Ba/F3 cells (2 × 10 5 /mL) was added and incubated in a 5% CO 2 incubator at 37 • C for 72 h as previously described [70]. Ba/F3 cells expressing BCR-ABL or the BCR-ABL T315I mutant were selected by culturing in RPMI medium containing 10% FBS, 100 units/mL penicillin, and 100 µg/mL streptomycin.…”
Section: Virus Production and Retrovirus Infectionmentioning
confidence: 99%
“…Denatured samples were resolved by SDS-PAGE and transferred to polyvinylidene difluoride (PVDF) membranes (Millipore, Billerica, MA). Membranes were probed using the designated antibodies and visualized with the ECL detection system (GE Healthcare, Little Chalfont, UK) as described previously [18]. In order to show the relative phosphorylation level of CREB, the band intensities of phosphorylated CREB were normalized with the band intensities of CREB by ImageJ.…”
Section: Preparation Of Nuclear Fractions and Immunoblottingmentioning
confidence: 99%
“…RNA was prepared using Sepazol (Nacalai Tesque). RT was performed using an oligo (dT) 20 primer (TOYOBO, Osaka, Japan) and 1 μg of total RNA for first-strand cDNA synthesis, as described previously [18]. Quantitative real-time PCR was performed using an iCycler detection system (Bio-Rad, Berkeley, CA, USA).…”
Section: Rna Isolation and Rt-pcr (Reverse Transcriptase-polymerase Chain Reaction)mentioning
confidence: 99%